Kerjasama BNPT dan Terrorism Prevention Branch (TPB) UNODC dalam Mencegah Paham Radikal dan Tindak Kejahatan Terorisme di Indonesia - Oktiana, Eldya; Putranti, Ika Riswanti; Basith Dir, Andi Akhmad (Journal of International Relations, 2018)
After the outbreak of terrorism case in 2002, the Government of Indonesia believesterrorism cases will not be solved by using hard approach only such as the police work,Indonesia must also have a body responsible for handling soft approach to prevent andsolve the radicalism. BNPT was formed in 2010 as a response. As a member of the UnitedNation, BNPT subsequently established a partnership with TPB UNODC which focusedon the issue of global terrorism. This research is intended to understand the role of TPBUNODC in a cooperation with BNPT on the prevention of radicalism and terrorism crimein Indonesia. This research uses qualitative method with descriptive-explanative type withliterature and technique study. To answer the question, this research used theconstructivism paradigm which is supported by the result of interview with the membersof BNPT RI and UNODC Indonesia. The results of this study indicated that thecooperation between BNPT and TPB UNODC helped Indonesia to develop the quality ofBNPT RI as an organization in terms of strategy, relation and capacity, supported byindicators listed in the UNODC report and with successful result of counter radicalizationand deradicalisation programmed.